The Results of Using Gamification and Growth Mindset to Develop English Reading Skills for Elementary Students - Wibooncharoensuk, Prempol; Klaimongkol, Yurawat (An Online Journal of Education, 2023)
The objectives of this research were 1) to compare the reading skills of students who received learning activities using gamification concepts with a growth mindset between experimental group students and the control group; 2) to compare reading skills before and after learning activities using gamification concepts with a growth mindset of experimental. The sample group consisted of 67 elementary school fourth-grade students under the Ramkhamheang University Demonstration School Elementary Level, divided into two groups: an experimental group of 31 people and a control group of 36 people. The research tools consisted of reading ability tests and teaching plans for English reading skills by using gaming concepts with a growth mindset. The researcher compared the learning achievement between the experimental group and the control group and compared the learning achievements of the experimental group before and after learning using Mean and Standard Deviation. The research results concluded that 1) The students who managed to learn by using gamification concepts in conjunction with the growth mindset, the experimental group students had reading skills after organizing learning activities by using gamification concepts together with the growth mindset was higher than the control group students. 2) The students who managed to learn by using the concept of gamification in conjunction with the growth mindset had higher reading skills than before the experiment.